The HAS‐BLED Score for Predicting Major Bleeding Risk in Anticoagulated Patients With Atrial Fibrillation: A Systematic Review and Meta‐analysis - Zhu, Wengen (Clin Cardiol, 2015)
Our objective was to compare the diagnostic accuracy between the HAS‐BLED score and any of HEMORR(2)HAGES, ATRIA, CHADS(2), or CHA(2)DS(2)‐VASc scores in anticoagulated patients with atrial fibrillation. We systematically searched the Cochrane Library, MEDLINE, PubMed, and Embase databases for relevant studies. Data were extracted and analyzed according to predefined clinical endpoints. Eleven studies were identified. Discrimination analysis demonstrates that HAS‐BLED has no significant C‐statistic differences for bleeding risk prediction compared with ATRIA or HEMORR(2)HAGES, but it has significant differences compared with CHADS(2) or CHA(2)DS(2)‐VASc. The significant positive net reclassification improvement and integrated discrimination improvement values also show that HAS‐BLED is superior to that of any of HEMORR(2)HAGES, ATRIA, CHADS(2), or CHA(2)DS(2)‐VASc scores. According to calibration analysis of HAS‐BLED, it overpredicts the risk of bleeding in the low (risk ratio [RR]: 1.16, 95% confidence interval [CI]: 0.63‐2.13, P = 0.64) risk stratification but underpredicts that in the moderate (RR: 0.66, 95% CI: 0.51‐0.86, P = 0.002) and high (RR: 0.88, 95% CI: 0.70‐1.10, P = 0.27) risk stratifications. The HAS‐BLED score not only performs better than the HEMORR(2)HAGES and ATRIA bleeding scores, but it also is superior to the CHADS(2) and CHA(2)DS(2)‐VASc stroke scores for bleeding prediction. The HAS‐BLED score should be the optimal choice to assess major bleeding risk in clinical practice.